A sol-gel preparation method of 45S5 bioactive glass and its product

By using phosphate-ethylene glycol esterides and nitrogen-containing carbon quantum dots, combined with calcium carbonate, sodium carbonate and sodium nitrite, the problems of long gel time, unstable oxide composition and low specific surface area of ​​45S5 bioactive glass were solved, and an efficient and safe production process was achieved.

CN118930022BActive Publication Date: 2025-03-18SHENYANG STOMATOLOGICAL HOSPITAL +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411437988.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-18
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing sol-gel method for preparing 45S5 bioactive glass has been used for too long gel time, the volatility of the raw material triethyl phosphate leads to unstable oxide components in the product, low specific surface area, and raw material safety problems.

Method used

Phosphoric acid-ethylene glycol esterides are used as the source of P2O5, nitrogen-containing carbon quantum dots are used to increase the specific surface area, and the combination of calcium carbonate, sodium carbonate and sodium nitrite is avoided to shorten the gel time.

Benefits of technology

It effectively increases the specific surface area of ​​45S5 bioactive glass, stabilizes the oxide composition, shortens the gel time, improves production efficiency, and avoids the use of nitrates, ensuring the safety of raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930022B_ABST
    Figure CN118930022B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of medical materials, and relates to a sol-gel preparation method and product of 45S5 bioactive glass. The preparation method comprises the following steps: (1) synthesis of phosphoric acid-ethylene glycol ester; (2) preparation of nitrogen-containing carbon quantum dots; (3) preparation of sol; (4) preparation of aqueous solution; (5) preparation of gel; and (6) heat treatment. The present invention also provides a 45S5 bioactive glass. In the sol-gel preparation method of the present invention, phosphoric acid-ethylene glycol ester is used as the source of P2O5 in the product, which can avoid the problem of difficult control of product phosphorus content and waste of raw materials caused by volatilization when triethyl phosphate is used as a raw material in the prior art. At the same time, nitrogen-containing carbon quantum dots are used, so that the specific surface area of ​​the prepared 45S5 bioactive glass is effectively improved. The present invention has the advantages of safe raw materials, short required gel time, stable oxide components in the product, and high specific surface area of ​​the prepared 45S5 bioactive glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to a sol-gel preparation method of 45S5 bioactive glass and a product thereof. Background Art

[0002] Bioactive glass is a bone tissue repair material with a special composition, good biocompatibility and bioactivity, and is degradable to a certain extent. 45S5 bioactive glass is a typical representative of the bioactive glass family. 45S5 bioactive glass is mainly composed of four oxides: silicon, calcium, sodium, and phosphorus. The molar ratio of SiO2, CaO, Na2O, and P2O5 is approximately (44-46): (22-26): (22-26): (5-7). After being implanted in the body, 45S5 bioactive glass can have a good combination with the surrounding bone tissue and promote the growth of bone tissue. It has great application prospects in bone tissue and soft tissue repair.

[0003] At present, the preparation methods of bioactive glass include melting method, sol-gel method and template method. Among them, the production of bioactive glass by sol-gel method has the advantages of low energy consumption, uniform and stable chemical composition of materials, and simple preparation method. However, there are still certain problems in the production of bioactive glass by sol-gel method. They mainly include: first, the gel time is long. Taking the preparation of 45S5 bioactive glass as an example, tetraethyl orthosilicate is usually used as a silicon source in the preparation process. After tetraethyl orthosilicate forms a sol, its gel time usually exceeds 5 hours. Long gel time will cause problems such as reduced production efficiency and increased energy consumption. Secondly, the amount of SiO2, CaO, Na2O and P2O5 contained in the product components and raw material components is inconsistent. This is because triethyl phosphate is usually used as the source of P2O5 in the product when preparing 45S5 bioactive glass. In the preparation process, triethyl phosphate will volatilize to a certain extent, which not only causes waste of raw materials, but also causes instability of the oxide component in the product. Third, although the specific surface area of ​​bioactive glass produced by the sol-gel method is higher than that of bioactive glass produced by the melting method, it is generally less than 300m 2 / g, and the low specific surface area is not conducive to the rapid hydration of bioactive glass to form hydroxyapatite. Finally, nitrate is a commonly used raw material for the preparation of 45S5 bioactive glass. However, the use of nitrate has problems such as cumbersome approval procedures and high storage and transportation safety costs, which requires finding raw materials to replace nitrate. Therefore, when using the sol-gel method to prepare bioactive glass, there are problems such as long gel time, unstable oxide components in the product due to the volatility of the raw material triethyl phosphate, low specific surface area of ​​the product bioactive glass, and raw material safety. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a sol-gel preparation method of 45S5 bioactive glass and its product.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a sol-gel preparation method of 45S5 bioactive glass, comprising the following steps:

[0006] (1) Synthesis of phosphoric acid-ethylene glycol ester:

[0007] Phosphorus pentoxide and ethylene glycol are mixed at a molar ratio of 1:6 under normal pressure, and the mixture is stirred and reacted at 80°C for 6 hours; the temperature of the reaction system is then raised to 110°C-140°C, and the mixture is stirred and reacted for 12 hours under vacuum conditions; the mixture is cooled to room temperature, and the reaction product is taken out under normal pressure, which is phosphoric acid-ethylene glycol ester;

[0008] (2) Preparation of nitrogen-containing carbon quantum dots:

[0009] In a 1% formaldehyde solution, melamine is added, and then triethanolamine is added dropwise to adjust the pH value of the liquid to 9; the mixed solution is stirred and reacted in a hydrothermal reactor at 80°C for 1 hour; then citric acid is added; the mixed solution mixed with citric acid is hydrothermally reacted at 180°C for 24 hours; after cooling to room temperature, the product after the reaction is filtered, and a brown-yellow transparent filtrate is retained; the brown-yellow transparent filtrate is dried, and the solid product obtained is collected, which is nitrogen-containing carbon quantum dots;

[0010] (3) Preparation of sol:

[0011] Mix water and tetraethyl orthosilicate in a molar ratio of 6:1, add nitric acid dropwise to adjust the pH value of the water to 2-4; then add phosphoric acid-ethylene glycol ester, stir at 60°C for 3-5 hours to form a transparent solution without stratification, which is the sol;

[0012] (4) Preparation of aqueous solution:

[0013] Calcium carbonate, sodium carbonate and water are mixed and stirred, and nitric acid is slowly added during the stirring process until the pH value of the solution is 2-4 to form a transparent solution; the nitrogen-containing carbon quantum dots prepared in step (2) are added to the transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0014] (5) Preparation of gel:

[0015] The sol prepared in step (3) is mixed with the aqueous solution prepared in step (4), and then a sodium nitrite solution having a weight concentration of 30% is added and stirred for 5 minutes to form a transparent, uniform and non-stratified solution; the solution is allowed to stand for 5-30 minutes to form a gel;

[0016] (6) Heat treatment:

[0017] The gel prepared in step (5) is dried at 60°C-80°C for 10 hours and then crushed. The crushed product is heat treated in a muffle furnace for 3 hours and cooled to room temperature to obtain 45S5 bioactive glass.

[0018] Furthermore, the acid value of the phosphoric acid-ethylene glycol ester obtained in step (1) is less than 0.05 mgKOH / g.

[0019] Furthermore, the molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution in step (2) is (1-1.2):1:1.

[0020] Furthermore, the nitric acid in step (3) and step (4) is a nitric acid aqueous solution with a weight concentration of 40%-68%.

[0021] Furthermore, the weight ratio of calcium carbonate to water in step (4) is 1:(6-10).

[0022] Furthermore, the weight ratio of the nitrogen-containing carbon quantum dots to calcium carbonate in step (4) is 1:(1-2).

[0023] Furthermore, the weight ratio of tetraethyl orthosilicate to phosphoric acid-ethylene glycol ester is 780:(245-221); the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:(22-18):(6-14); the molar numbers of calcium carbonate, sodium carbonate and sodium nitrite satisfy the following relationship: (molar number of sodium nitrite ÷ 2 + molar number of sodium carbonate) ÷ molar number of calcium carbonate = 25 / 24.

[0024] Furthermore, the pulverized product is heat treated in a muffle furnace at a temperature of 700°C-800°C.

[0025] The present invention also provides a 45S5 bioactive glass prepared by the above method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. In the sol-gel preparation method of the present invention, phosphoric acid-ethylene glycol ester is used as the source of P2O5 in the product, which can avoid the problem of difficult control of product phosphorus content and waste of raw materials due to volatilization when triethyl phosphate is used as the raw material in the prior art.

[0028] 2. Nitrogen-containing carbon quantum dots are used in the sol-gel preparation method of the present invention. The nitrogen-containing carbon quantum dots are nanoparticles. During the heat treatment of the prepared gel, the nitrogen-containing carbon quantum dots are burned to form pores, thereby effectively improving the specific surface area of ​​the prepared 45S5 bioactive glass.

[0029] 3. The use of calcium carbonate and sodium carbonate in the present invention avoids the direct use of nitrates; the use of sodium nitrite solution reduces the gel time of preparing 45S5 bioactive glass by the traditional gel method from more than 5 hours to less than half an hour, effectively improving the production efficiency.

[0030] In summary, the sol-gel preparation method of the present invention has the advantages of safe raw materials, short gelation time, stable oxide components in the product, and high specific surface area of ​​the prepared 45S5 bioactive glass. It can be used in the fields of bone tissue and soft tissue repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the X-ray diffraction spectrum of the 45S5 bioactive glass prepared in Example 1. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Example 1

[0034] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0035] (1) Synthesis of phosphoric acid-ethylene glycol ester:

[0036] 142 g of phosphorus pentoxide and 372 g of ethylene glycol (molar ratio 1:6) were mixed under normal pressure, and the mixture was stirred and reacted at 80°C for 6 hours; the temperature of the reaction system was then raised to 130°C, and the mixture was stirred and reacted for 12 hours under vacuum; the mixture was cooled to room temperature, and the reaction product, phosphoric acid-ethylene glycol ester, was taken out under normal pressure;

[0037] The prepared phosphoric acid-ethylene glycol ester is a mixture of phosphoric acid esters such as triethylene glycol phosphate, and the acid value of the phosphoric acid-ethylene glycol ester is less than 0.05 mgKOH / g;

[0038] (2) Preparation of nitrogen-containing carbon quantum dots:

[0039] In 600 grams of 1% formaldehyde solution, 25 grams of melamine are added, and then triethanolamine is added dropwise to adjust the pH value of the liquid to 9; the mixed solution is stirred and reacted in a hydrothermal reactor at 80°C for 1 hour; then 38 grams of citric acid is added (the molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution is 1:1:1); the mixture mixed with citric acid is hydrothermally reacted at 180°C for 24 hours; after cooling to room temperature, the reaction product is filtered to retain a brown-yellow transparent filtrate; the brown-yellow transparent filtrate is dried, and the solid product obtained is collected, which is nitrogen-containing carbon quantum dots, and the yield is 64%;

[0040] (3) Preparation of sol:

[0041] 108 g of water and 208 g of tetraethyl orthosilicate (molar ratio 6:1) were mixed, and 68% nitric acid was added dropwise to adjust the pH value of the water to 2; then 61 g of phosphoric acid-ethylene glycol ester (the weight ratio of tetraethyl orthosilicate to phosphoric acid-ethylene glycol ester was 780:228) was added, and stirred at 60°C for 3 hours to form a transparent solution without stratification, which was the sol;

[0042] (4) Preparation of aqueous solution:

[0043] 53 grams of calcium carbonate, 52 grams of sodium carbonate and 318 grams of water were mixed (the weight ratio of calcium carbonate to water was 1:6); and stirred, and 65% nitric acid was slowly added during the stirring process until the pH value of the solution was 2 to form a transparent solution; 53 grams of nitrogen-containing carbon quantum dots (the weight ratio of nitrogen-containing carbon quantum dots to calcium carbonate was 1:1) were added to the above transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0044] (5) Preparation of gel:

[0045] The sol was mixed with the aqueous solution, and then 31 g of a sodium nitrite solution with a weight concentration of 30% was added and stirred for 5 minutes to form a uniform non-stratified solution; the solution was allowed to stand for 30 minutes to form a gel.

[0046] (6) Heat treatment:

[0047] The prepared gel was dried at 70°C for 10 hours and then crushed; the crushed product was heat treated at 700°C in a muffle furnace for 3 hours and cooled to room temperature to obtain 45S5 bioactive glass. The X-ray diffraction spectrum of the prepared 45S5 bioactive glass is shown in Figure 1 shown.

[0048] In Example 1, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:22:6.

[0049] The molar numbers of calcium carbonate, sodium carbonate and sodium nitrite in Example 1 satisfy the following relationship: (molar number of sodium nitrite ÷ 2 + molar number of sodium carbonate) ÷ molar number of calcium carbonate = 25 / 24.

[0050] The theoretical molar percentages of SiO2, CaO, Na2O and P2O5 were calculated for the 45S5 bioactive glass prepared in Example 1, and the actual molar percentages of the above oxides in the prepared 45S5 bioactive glass were measured by X-ray fluorescence spectroscopy. The calculated theoretical values ​​and the measured values ​​are shown in Table 1: ;

[0051] As can be seen from Table 1, according to the preparation method of the present invention, the measured values ​​and theoretical values ​​of the molar composition of each oxide in the 45S5 bioactive glass obtained are basically consistent. The oxide components in the product are stable.

[0052] At the same time, the specific surface area of ​​the prepared 45S5 bioactive glass was measured, and its specific surface area reached 386m 2 / g, with a higher specific surface area.

[0053] The prepared 45S5 bioactive glass was immersed in Ringer solution to determine its in vitro degradation performance. The weight loss of the 45S5 bioactive glass prepared in this example reached 25% in 3 days, and the reactivity was good.

[0054] In summary, the 45S5 bioactive glass prepared in this embodiment has the advantages of stable oxide components in the product, high specific surface area, and high reactivity. At the same time, the gelation time in the preparation process is only 30 minutes, the gelation time is short, and the use of nitrate is avoided, and the raw materials are safe.

[0055] Example 2

[0056] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0057] (1) Synthesis of phosphoric acid-ethylene glycol ester:

[0058] 142 g of phosphorus pentoxide and 372 g of ethylene glycol (molar ratio 1:6) were mixed under normal pressure, and the mixture was stirred and reacted at 80°C for 6 hours; the temperature of the reaction system was then raised to 140°C, and the mixture was stirred and reacted for 12 hours under vacuum conditions; the mixture was cooled to room temperature, and the reaction product, namely phosphoric acid-ethylene glycol ester, was taken out under normal pressure;

[0059] The prepared phosphoric acid-ethylene glycol ester is a mixture of phosphoric acid esters such as triethylene glycol phosphate, and the acid value of the phosphoric acid-ethylene glycol ester is less than 0.05 mgKOH / g;

[0060] (2) Preparation of nitrogen-containing carbon quantum dots:

[0061] In 600 grams of 1% formaldehyde solution, add 21 grams of melamine, and then add triethanolamine to adjust the pH value of the liquid to 9; stir the mixture in a hydrothermal reactor at 80°C for 1 hour; then add 32 grams of citric acid (the molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution is 1.2:1:1); the mixture mixed with citric acid is hydrothermally reacted at 180°C for 24 hours; after cooling to room temperature, filter the reaction product and retain the brown-yellow transparent filtrate. The brown-yellow transparent filtrate is dried and the solid product obtained is collected, which is nitrogen-containing carbon quantum dots with a yield of 73%;

[0062] (3) Preparation of sol:

[0063] 108 g of water and 208 g of tetraethyl orthosilicate (molar ratio 6:1) were mixed, and 68% nitric acid was added dropwise to adjust the pH value of the water to 4; then 59 g of phosphoric acid-ethylene glycol ester (the weight ratio of tetraethyl orthosilicate to phosphoric acid-ethylene glycol ester was 780:221) was added, and stirred at 60°C for 5 hours to form a transparent solution without stratification, which was the sol;

[0064] (4) Preparation of aqueous solution:

[0065] 53 grams of calcium carbonate, 43 grams of sodium carbonate and 318 grams of water were mixed (the weight ratio of calcium carbonate to water was 1:6); and stirred, and 40% nitric acid was slowly added during the stirring process until the pH value of the solution was 2, forming a transparent solution; 106 grams of nitrogen-containing carbon quantum dots (the weight ratio of nitrogen-containing carbon quantum dots to calcium carbonate was 1:2) were added to the above transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0066] (5) Preparation of gel:

[0067] The sol was mixed with the aqueous solution, and then 72 g of a sodium nitrite solution with a weight concentration of 30% was added and stirred for 5 minutes to form a uniform non-stratified solution; the solution was allowed to stand for 5 minutes to form a gel;

[0068] (6) Heat treatment:

[0069] The prepared gel was dried at 70°C for 10 hours and then crushed. The crushed product was heat treated at 750°C for 3 hours in a muffle furnace and cooled to room temperature to obtain 45S5 bioactive glass.

[0070] In Example 2, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:18:14.

[0071] In Example 2, the moles of calcium carbonate, sodium carbonate and sodium nitrite satisfy the following relationship: (moles of sodium nitrite ÷ 2 + moles of sodium carbonate) ÷ moles of calcium carbonate = 25 / 24.

[0072] The theoretical molar percentages of SiO2, CaO, Na2O and P2O5 were calculated for the 45S5 bioactive glass prepared in Example 2, and the actual molar percentages of the above oxides in the prepared 45S5 bioactive glass were measured by X-ray fluorescence spectroscopy. The calculated theoretical values ​​and the measured values ​​are shown in Table 2:

[0073] ;

[0074] As can be seen from Table 1, according to the preparation method of the present invention, the measured values ​​and theoretical values ​​of the molar composition of each oxide in the 45S5 bioactive glass obtained are basically consistent. The oxide components in the product are stable.

[0075] The specific surface area of ​​the prepared 45S5 bioactive glass was measured and its specific surface area reached 459 m 2 / g, with a higher specific surface area.

[0076] The prepared 45S5 bioactive glass was immersed in Ringer solution to determine its in vitro degradation performance. The weight loss of the 45S5 bioactive glass prepared in this example reached 32% in 3 days, and the reactivity was good.

[0077] In summary, the 45S5 bioactive glass prepared in this embodiment has the advantages of stable oxide components in the product, high specific surface area, and high reactivity. At the same time, the gelation time in the preparation process is only 5 minutes, the gelation time is short, and the use of nitrate is avoided, and the raw materials are safe.

[0078] Example 3

[0079] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0080] (1) Synthesis of phosphoric acid-ethylene glycol ester:

[0081] 142 grams of phosphorus pentoxide and 372 grams of ethylene glycol (molar ratio 1:6) were mixed under normal pressure, and the mixture was stirred and reacted at 80°C for 6 hours; the temperature of the reaction system was then raised to 110°C, and the mixture was stirred and reacted for 12 hours under vacuum conditions; the temperature was cooled to room temperature, and the reaction product was taken out under normal pressure, which was phosphoric acid-ethylene glycol ester; the prepared phosphoric acid-ethylene glycol ester was a mixture of phosphoric acid esters such as triethylene glycol phosphate, and the acid value of the phosphoric acid-ethylene glycol ester was less than 0.05 mgKOH / g;

[0082] (2) Preparation of nitrogen-containing carbon quantum dots:

[0083] In 600 grams of 1% formaldehyde solution, 23 grams of melamine are added, and then triethanolamine is added dropwise to adjust the pH value of the liquid to 9; the mixed solution is stirred and reacted in a hydrothermal reactor at 80°C for 1 hour; then 35 grams of citric acid is added (the molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution is 1.1:1:1); the mixture mixed with citric acid is hydrothermally reacted at 180°C for 24 hours; after cooling to room temperature, the reaction product is filtered to retain a brown-yellow transparent filtrate; the brown-yellow transparent filtrate is dried, and the solid product obtained is collected, which is nitrogen-containing carbon quantum dots, with a yield of 68%;

[0084] (3) Preparation of sol:

[0085] 108 g of water and 208 g of tetraethyl orthosilicate (molar ratio 6:1) were mixed, and 58% nitric acid was added dropwise to adjust the pH value of the water to 3; then 63 g of phosphoric acid-ethylene glycol ester (the weight ratio of tetraethyl orthosilicate to phosphoric acid-ethylene glycol ester was 780:237) was added, and stirred at 60°C for 4 hours to form a transparent solution without stratification, which was the sol;

[0086] (4) Preparation of aqueous solution:

[0087] 53 grams of calcium carbonate, 48 grams of sodium carbonate and 318 grams of water were mixed (the weight ratio of calcium carbonate to water was 1:6); and stirred, and 58% nitric acid was slowly added during the stirring process until the pH value of the solution was 2, forming a transparent solution; 80 grams of nitrogen-containing carbon quantum dots (the weight ratio of nitrogen-containing carbon quantum dots to calcium carbonate was 1:1.5) were added to the above transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0088] (5) Preparation of gel:

[0089] The sol was mixed with the aqueous solution, and then 51 g of a sodium nitrite solution with a weight concentration of 30% was added and stirred for 5 minutes to form a uniform non-stratified solution; the solution was allowed to stand for 15 minutes to form a gel;

[0090] (6) Heat treatment:

[0091] The prepared gel was dried at 70°C for 10 hours and then crushed. The crushed product was heat treated at 800°C for 3 hours in a muffle furnace and cooled to room temperature to obtain 45S5 bioactive glass.

[0092] In Example 3, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:20:10.

[0093] In Example 3, the moles of calcium carbonate, sodium carbonate and sodium nitrite satisfy the following relationship: (moles of sodium nitrite ÷ 2 + moles of sodium carbonate) ÷ moles of calcium carbonate = 25 / 24.

[0094] The theoretical molar percentages of SiO2, CaO, Na2O and P2O5 were calculated for the 45S5 bioactive glass prepared in Example 2, and the actual molar percentages of the above oxides in the prepared 45S5 bioactive glass were measured by X-ray fluorescence spectroscopy. The calculated theoretical values ​​and the measured values ​​are shown in Table 3:

[0095] ;

[0096] As can be seen from Table 3, according to the preparation method of the present invention, the measured values ​​and theoretical values ​​of the molar composition of each oxide in the 45S5 bioactive glass obtained are basically consistent. The oxide components in the product are stable.

[0097] The specific surface area of ​​the prepared 45S5 bioactive glass was measured and found to be 418 m 2 / g, with a higher specific surface area.

[0098] The prepared 45S5 bioactive glass was immersed in Ringer solution to determine its in vitro degradation performance. The weight loss of the 45S5 bioactive glass prepared in this example reached 28% in 3 days, and the reactivity was good.

[0099] In summary, the 45S5 bioactive glass prepared in this embodiment has the advantages of stable oxide components in the product, high specific surface area, and high reactivity. At the same time, the gelation time in the preparation process is only 15 minutes, the gelation time is short, and the use of nitrate is avoided, and the raw materials are safe.

[0100] Comparative Example 1

[0101] The difference between this comparative example and Example 1 is that the phosphoric acid-ethylene glycol ester in the reaction raw material is replaced by triethyl phosphate.

[0102] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0103] (1) Preparation of nitrogen-containing carbon quantum dots: same as in Example 1.

[0104] (2) Preparation of sol:

[0105] Mix 108 g of water and 208 g of tetraethyl orthosilicate (molar ratio 6:1), and add 68% nitric acid to adjust the pH value of the water to 2. Then add 48 g of triethyl phosphate and stir at 60°C for 3 hours to form a transparent solution without stratification, which is the sol;

[0106] (3) Preparation of aqueous solution: same as in Example 1.

[0107] (4) Preparation of gel: same as in Example 1.

[0108] (5) Heat treatment: same as in Example 1.

[0109] In Comparative Example 1, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:22:6.

[0110] The molar numbers of calcium carbonate, sodium carbonate and sodium nitrite in Comparative Example 1 satisfy the following relationship: (molar number of sodium nitrite ÷ 2 + molar number of sodium carbonate) ÷ molar number of calcium carbonate = 25 / 24.

[0111] The theoretical molar percentages of SiO2, CaO, Na2O and P2O5 in the 45S5 bioactive glass prepared in Comparative Example 1 were calculated, and the actual molar percentages of the above oxides in the prepared 45S5 bioactive glass were measured by X-ray fluorescence spectroscopy. The calculated theoretical values ​​and the measured values ​​are shown in Table 4:

[0112] ;

[0113] As can be seen from Table 4, according to the experimental steps of Comparative Example 1, using the commonly used triethyl phosphate raw material, the content of phosphorus oxide in the prepared product is very low. During the product preparation process, the loss of phosphorus is very large. The phosphorus content in the prepared product does not meet the requirements for phosphorus content in the commonly used 45S5 bioglass.

[0114] Comparative Example 2

[0115] The difference between this comparative example and Example 1 is that in the synthesis of phosphoric acid-ethylene glycol ester, the temperature of the reaction system is 100°C.

[0116] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0117] (1) Synthesis of phosphoric acid-ethylene glycol ester: The difference from Example 1 is that the reaction is continuously stirred at 80°C for 6 hours; then the temperature of the reaction system is continuously raised to 100°C, and the rest is the same as Example 1. The acid value of the prepared phosphoric acid-ethylene glycol ester is greater than 1 mgKOH / g.

[0118] (2) Preparation of nitrogen-containing carbon quantum dots: same as in Example 1.

[0119] (3) Preparation of sol: same as in Example 1.

[0120] (4) Preparation of aqueous solution: same as in Example 1.

[0121] (5) Preparation of gel: When the sol is mixed with the aqueous solution, a white insoluble substance appears.

[0122] It can be seen from Comparative Example 2 that in the preparation process of phosphoric acid-ethylene glycol ester, if the reaction temperature is lower than 110° C., the esterification reaction is incomplete, and white insoluble matter formed by calcium ions and phosphate radicals will be produced in the later gel preparation process, resulting in the inability to prepare a transparent and homogeneous gel.

[0123] Comparative Example 3

[0124] The difference between this comparative example and Example 1 is that no nitrogen-containing carbon quantum dots are used in the reaction raw materials.

[0125] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0126] (1) Synthesis of phosphoric acid-ethylene glycol ester: Same as Example 1.

[0127] (2) Preparation of sol: same as in Example 1.

[0128] (3) Preparation of aqueous solution: Mix 53 g of calcium carbonate, 52 g of sodium carbonate and 318 g of water (the weight ratio of calcium carbonate to water is 1:6). Stir and slowly add 65% nitric acid during stirring until the pH value of the solution reaches 2 to form a transparent solution; ultrasonically treat for 10 minutes and stir for another 10 minutes to form a uniform and stable liquid;

[0129] (4) Preparation of gel: same as in Example 1.

[0130] (5) Heat treatment: same as in Example 1.

[0131] In Comparative Example 3, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:22:6.

[0132] The molar numbers of calcium carbonate, sodium carbonate and sodium nitrite in Comparative Example 3 satisfy the following relationship: (molar number of sodium nitrite ÷ 2 + molar number of sodium carbonate) ÷ molar number of calcium carbonate = 25 / 24.

[0133] The theoretical molar percentages of SiO2, CaO, Na2O and P2O5 in the 45S5 bioactive glass prepared in Comparative Example 3 were calculated, and the actual molar percentages of the above oxides in the prepared 45S5 bioactive glass were measured by X-ray fluorescence spectroscopy. The calculated theoretical values ​​and the measured values ​​are shown in Table 5:

[0134] ;

[0135] As can be seen from Table 5, according to the preparation method of Comparative Example 3, the measured values ​​and theoretical values ​​of the molar composition of each oxide in the 45S5 bioactive glass obtained are basically consistent.

[0136] The specific surface area of ​​the prepared 45S5 bioactive glass was measured and found to be 123 m 2 / g, and the specific surface area is low.

[0137] The prepared 45S5 bioactive glass was immersed in Ringer solution to determine its in vitro degradation performance, and it was found that the weight loss of the 45S5 bioactive glass prepared in this comparative example reached 13% in 3 days. The 45S5 bioactive glass prepared in this comparative example has low reactivity.

[0138] Comparative Example 4

[0139] In this comparative example, the weight concentration of nitric acid used in the preparation of the sol was 30%, and the molar ratio of water to tetraethyl orthosilicate was 7: 1. In the preparation of the aqueous solution, nitric acid with a weight concentration of 35% was used.

[0140] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0141] (1) Synthesis of phosphoric acid-ethylene glycol ester: Same as Example 1.

[0142] (2) Preparation of nitrogen-containing carbon quantum dots: same as in Example 1.

[0143] (3) Preparation of sol: 126 g of water and 208 g of tetraethyl orthosilicate (molar ratio 7:1) were mixed, and 30% nitric acid was added dropwise to adjust the pH value of the water to 2; then 61 g of phosphoric acid-ethylene glycol ester (the weight ratio of tetraethyl orthosilicate to phosphoric acid-ethylene glycol ester was 780:228) was added, and stirred at 60°C for 3 hours to form a transparent solution without stratification, which was the sol;

[0144] (4) Preparation of aqueous solution: 53 g of calcium carbonate, 52 g of sodium carbonate and 318 g of water were mixed (the weight ratio of calcium carbonate to water was 1:6); the mixture was stirred, and 35% nitric acid was slowly added during the stirring process until the pH value of the solution reached 2, thereby forming a transparent solution; 53 g of nitrogen-containing carbon quantum dots (the weight ratio of nitrogen-containing carbon quantum dots to calcium carbonate was 1:1) were added to the above transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0145] (5) Preparation of gel: Same as Example 1, but no gel was formed after standing for 30 minutes.

[0146] It can be seen that in the preparation process, when the weight concentration of nitric acid is lower than 40% and the molar ratio of water to tetraethyl orthosilicate is greater than 6:1, gel cannot be generated, that is, 45S5 bioactive glass cannot be prepared.

[0147] Comparative Example 5

[0148] In this comparative example, 10 g of a sodium nitrite solution having a weight concentration of 30% was added during the preparation of the gel.

[0149] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0150] (1) Synthesis of phosphoric acid-ethylene glycol ester: Same as Example 1.

[0151] (2) Preparation of nitrogen-containing carbon quantum dots: same as in Example 1.

[0152] (3) Preparation of sol: same as in Example 1.

[0153] (4) Preparation of aqueous solution: 53 g of calcium carbonate, 57 g of sodium carbonate and 318 g of water were mixed (the weight ratio of calcium carbonate to water was 1:6); and stirred. During the stirring process, 65% nitric acid was slowly added until the pH value of the solution was 2 to form a transparent solution; 53 g of nitrogen-containing carbon quantum dots (the weight ratio of nitrogen-containing carbon quantum dots to calcium carbonate was 1:1) was added to the above transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0154] (5) Preparation of gel: The sol was mixed with the aqueous solution, and then 10 g of a 30% sodium nitrite solution was added and stirred for 5 minutes to form a uniform non-stratified solution. After standing for 3 hours, no gel was formed.

[0155] In Comparative Example 5, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:24:2.

[0156] In Comparative Example 5, the molar numbers of calcium carbonate, sodium carbonate and sodium nitrite satisfy the following relationship: (the molar number of sodium nitrite ÷ 2 + the molar number of sodium carbonate) ÷ the molar number of calcium carbonate = 25 / 24.

[0157] In this comparative example, since the amount of sodium nitrite solution added was too small, the molar ratio of sodium carbonate to sodium nitrite was not in the range of (22-18): (6-14), and no gel was generated, that is, 45S5 bioactive glass could not be prepared.

[0158] Comparative Example 6

[0159] In this comparative example, 112 g of a sodium nitrite solution having a weight concentration of 30% was added during the preparation of the gel.

[0160] A sol-gel preparation method for 45S5 bioactive glass comprises the following steps:

[0161] (1) Synthesis of phosphoric acid-ethylene glycol ester: Same as Example 1.

[0162] (2) Preparation of nitrogen-containing carbon quantum dots: same as in Example 1.

[0163] (3) Preparation of sol: same as in Example 1.

[0164] (4) Preparation of aqueous solution: 53 g of calcium carbonate, 33 g of sodium carbonate and 318 g of water were mixed (the weight ratio of calcium carbonate to water was 1:6); and stirred. During the stirring process, 65% nitric acid was slowly added until the pH value of the solution was 2, forming a transparent solution; 53 g of nitrogen-containing carbon quantum dots (the weight ratio of nitrogen-containing carbon quantum dots to calcium carbonate was 1:1) was added to the above transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid;

[0165] (5) Preparation of gel: Mix the sol with the aqueous solution, then add 112 g of a 30% by weight sodium nitrite solution and stir; a gel is formed within two minutes.

[0166] In Comparative Example 5, the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:14:22.

[0167] The molar numbers of calcium carbonate, sodium carbonate and sodium nitrite in Comparative Example 5 satisfy the following relationship: (molar number of sodium nitrite ÷ 2 + molar number of sodium carbonate) ÷ molar number of calcium carbonate = 25 / 24.

[0168] In this comparative example, due to excessive addition of sodium nitrite solution, the gel was formed too quickly and the solution was not mixed evenly, so that 45S5 bioactive glass could not be prepared.

[0169] Comparative Example 7

[0170] The molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution during the preparation of nitrogen-containing carbon quantum dots is 1:2:2.

[0171] The specific preparation process of the nitrogen-containing carbon quantum dots in this comparative example is:

[0172] In 600 grams of 1% formaldehyde solution, 50 grams of melamine are added, and then triethanolamine is added dropwise to adjust the pH value of the liquid to 9; the mixed solution is stirred and reacted in a hydrothermal reactor at 80°C for 1 hour; then 76 grams of citric acid are added (the molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution is 1:2:2); the mixture mixed with citric acid is hydrothermally reacted at 180°C for 24 hours; after cooling to room temperature, the reaction product is filtered to retain the brown-yellow transparent filtrate; the brown-yellow transparent filtrate is dried and the solid product obtained is collected, which is nitrogen-containing carbon quantum dots with a yield of 34%.

[0173] In this comparative example, the ratio of formaldehyde to melamine is not 1:1, resulting in incomplete reaction of melamine. The final product contains more precipitates and the product yield is low.

[0174] Comparative Example 8

[0175] The molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution during the preparation of nitrogen-containing carbon quantum dots is 2:1:2.

[0176] The specific preparation process of the nitrogen-containing carbon quantum dots in this comparative example is:

[0177] In 600 grams of 1% formaldehyde solution, add 50 grams of melamine, and then add triethanolamine to adjust the pH value of the liquid to 9; stir the mixture in a hydrothermal reactor at 80°C for 1 hour; then add 76 grams of citric acid (the molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution is 2:1:2); the mixture mixed with citric acid is hydrothermally reacted at 180°C for 24 hours. After cooling to room temperature, filter the reaction product and retain the brown-yellow transparent filtrate. Dry the brown-yellow transparent filtrate and collect the solid product, which is nitrogen-containing carbon quantum dots, with a yield of 45%.

[0178] In this comparative example, the ratio of formaldehyde to melamine is not 1:1, resulting in incomplete reaction of melamine. The final product contains more precipitates and the product yield is low.

[0179] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made on the basis of the present invention. Therefore, these modifications or improvements made on the basis of not departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A sol-gel preparation method for 45S5 bioactive glass, characterized in that: The following steps are involved: (1) Synthesis of phosphoric acid-ethylene glycol ester: Phosphorus pentoxide and ethylene glycol are mixed at a molar ratio of 1:6 under normal pressure, and the mixture is stirred and reacted at 80°C for 6 hours; the temperature of the reaction system is then raised to 110°C-140°C, and the mixture is stirred and reacted for 12 hours under vacuum conditions; the mixture is cooled to room temperature, and the reaction product is taken out under normal pressure, which is phosphoric acid-ethylene glycol ester; (2) Preparation of nitrogen-containing carbon quantum dots: In a 1% formaldehyde solution, melamine is added, and then triethanolamine is added dropwise to adjust the pH value of the liquid to 9; the mixed solution is stirred and reacted in a hydrothermal reactor at 80°C for 1 hour; then citric acid is added; the mixed solution mixed with citric acid is hydrothermally reacted at 180°C for 24 hours; after cooling to room temperature, the product after the reaction is filtered, and a brown-yellow transparent filtrate is retained; the brown-yellow transparent filtrate is dried, and the solid product obtained is collected, which is nitrogen-containing carbon quantum dots; (3) Preparation of sol: Mix water and tetraethyl orthosilicate in a molar ratio of 6:1, add nitric acid dropwise to adjust the pH value of the water to 2-4; then add phosphoric acid-ethylene glycol ester, stir at 60°C for 3-5 hours to form a transparent solution without stratification, which is the sol; (4) Preparation of aqueous solution: Calcium carbonate, sodium carbonate and water are mixed and stirred, and nitric acid is slowly added during the stirring process until the pH value of the solution is 2-4 to form a transparent solution; the nitrogen-containing carbon quantum dots prepared in step (2) are added to the transparent solution, ultrasonically treated for 10 minutes, and stirred for another 10 minutes to form a uniform and stable liquid; (5) Preparation of gel: The sol prepared in step (3) is mixed with the aqueous solution prepared in step (4), and then a sodium nitrite solution having a weight concentration of 30% is added and stirred for 5 minutes to form a transparent, uniform and non-stratified solution; the solution is allowed to stand for 5-30 minutes to form a gel; (6) Heat treatment: The gel prepared in step (5) is dried at 60°C-80°C for 10 hours and then crushed; the crushed product is heat treated in a muffle furnace for 3 hours and cooled to room temperature to obtain 45S5 bioactive glass; The weight ratio of tetraethyl orthosilicate to phosphoric acid-ethylene glycol ester is 780:(245-221); the molar ratio of tetraethyl orthosilicate, calcium carbonate, sodium carbonate and sodium nitrite is 45:24:(22-18):(6-14); the molar numbers of calcium carbonate, sodium carbonate and sodium nitrite satisfy the following relationship: (molar number of sodium nitrite ÷ 2 + molar number of sodium carbonate) ÷ molar number of calcium carbonate = 25 / 24.

2. The sol-gel preparation method of 45S5 bioactive glass according to claim 1, characterized in that: The acid value of the phosphoric acid-ethylene glycol ester obtained in step (1) is less than 0.05 mgKOH / g.

3. The sol-gel preparation method of 45S5 bioactive glass according to claim 1, characterized in that: The molar ratio of pure formaldehyde, melamine and citric acid in the 1% formaldehyde solution in step (2) is (1-1.2):1:

1.

4. The sol-gel preparation method of 45S5 bioactive glass according to claim 1, characterized in that: The nitric acid in step (3) and step (4) is an aqueous nitric acid solution with a weight concentration of 40% to 68%.

5. The sol-gel preparation method of 45S5 bioactive glass according to claim 1, characterized in that: The weight ratio of calcium carbonate to water in step (4) is 1:(6-10).

6. The sol-gel preparation method of 45S5 bioactive glass according to claim 1, characterized in that: The weight ratio of the nitrogen-containing carbon quantum dots to calcium carbonate in the step (4) is 1:(1-2).

7. The sol-gel preparation method of 45S5 bioactive glass according to claim 1, characterized in that: The product after pulverization in the step (6) is heat treated in a muffle furnace at a temperature of 700° C.-800° C.

8. 45S5 bioactive glass prepared by the sol-gel preparation method of 45S5 bioactive glass as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Medical magnesium alloy surface mesoporous biological glass coating and preparation method

    CN103495202A

  • Sol-gel Bioactive Glass Initial Solution And A Preparation Method Of The Sol-gel Bioactive Glass And The Prepared Sol-gel Bioactive Glass Initial Solution

    CN103880285A

  • Sulfur quantum dot and phosphate mesoporous glass compound and preparation method thereof

    CN105693096A